The politics of informality in criminal procedures - Brodersen, Kei Hannah (International journal of law, crime and justice, 2023)
The tension between formality and informality is intrinsic to the implementation of criminal law. Criminal procedures in fact always happen on a continuum between formality and informality, where the different actors involved (police officers and other street-level bureaucrats, prosecutors, judges, experts, defense lawyers, etc.) continuously perform and negotiate (in)formality. This special issue explores these "politics of (in)formality" in different criminal law settings and from different disciplinary perspectives. The different empirical contributions explore the continuum between formality and informality as well as practices of informalization in two different levels of the criminal justice system: police investigations and court proceedings.